Role of Parkin-mediated mitophagy in the protective effect of polydatin in sepsis-induced acute kidney injury - Youguang Gao (Journal of Translational Medicine, 2020)
Abstract Background We have reported that polydatin (PD) alleviates mitochondrial dysfunction in rat models of sepsis-induced acute kidney injury (SI-AKI), but the mechanism is not well understood. Here, we investigated the role of Parkin-mediated mitophagy in the protective effects of PD in SI-AKI in mice. Methods Sepsis was induced in the mice by caecal ligation and puncture. Mitophagy was determined by mitochondrial mass. NLRP3 inflammasome activation was determined by NLRP3, ASC and caspase-1. Mitophagy was blocked by treatment with mitochondrial division inhibitor-1 and Parkin knockout. Key results PD treatment increased the sepsis-induced loss of mitochondrial mass, indicating the upregulation of mitophagy. Furthermore, PD treatment mediated Parkin translocation from the cytoplasm to the mitochondria. This suggests that Parkin-mediated mitophagy is an underlying mechanism. This was confirmed by the suppression of PD-induced mitophagy in Parkin−/− mice and in mice that were treated with a mitophagy inhibitor. PD-induced Parkin translocation and mitophagy were blocked by inhibiting SIRT1; thus, activation of SIRT1 might be an important molecular mechanism that is triggered by PD. Additionally, PD treatment protected against sepsis-induced kidney injury. These effects were blocked by inhibition of Parkin-dependent mitophagy. Furthermore, PD also protected against mitochondrial dysfunction and mitochondria-dependent apoptosis, and the effect was blocked when Parkin-dependent mitophagy was inhibited. Finally, PD suppressed NLRP3 inflammasome activation that was also dependent on Parkin-mediated mitophagy. Conclusions These findings indicate that Parkin-mediated mitophagy is important for the protective effect of PD in SI-AKI, and the underlying mechanisms include the inhibition of mitochondrial dysfunction and NLRP3 inflammasome activation.